Mutations of PQBP1 in Renpenning syndrome promote ubiquitin-mediated degradation of FMRP and cause synaptic dysfunction. (10th January 2017) - Zhang, Xiao-Yan; Qi, Junxia; Shen, Yu-Qian; Liu, Xian; Liu, An; Zhou, Zikai; Han, Junhai; Zhang, Zi Chao
Abstract: Renpenning syndrome is a group of X-linked intellectual disability syndromes caused by mutations in human polyglutamine-binding protein 1 ( PQBP1 ) gene. Little is known about the molecular pathogenesis of the various mutations that cause the notable variability in patients. In this study, we examine the cellular and synaptic functions of the most common mutations found in the patients: c.461_462delAG, c.459_462delAGAG and c.463_464dupAG in an AG hexamer in PQBP1 exon 4. We discovered that PQBP1 c.459_462delAGAG and c.463_464dupAG mutations encode a new C-terminal epitope that preferentially binds non-phosphorylated fragile X mental retardation protein (FMRP) and promotes its ubiquitin-mediated degradation. Impairment of FMRP function up-regulates its targets such as MAP1B, and disrupts FMRP-dependent synaptic scaling in primary cultured neurons. In Drosophila neuromuscular junction model, PQBP1 c.463_464dupAG transgenic flies showed remarkable defects of synaptic over-growth, which can be rescued by exogenously expressing dFMRP. Our data strongly support a gain-of-function pathogenic mechanism of PQBP1 c.459_462delAGAG and c.463_464dupAG mutations, and suggest that therapeutic strategies to restore FMRP function may be beneficial for those patients.